Evaluation Of The Physical Training Program Of The Badminton Achievement Club In Bengkulu City - Bogy Restu Ilahi; Hadiwinarto Hadiwinarto; Sheren Dwi Oktaria (UNIB Press, 2020)
The purpose of this study was to evaluate the badminton club performance coaching physical training program. This research was conducted at the badminton coaching club Bengkulu city in 2021. In this study using the CIPP Model with survey research methods. Data obtained through observation, questionnaires, interviews, and documentation study. This study uses non-statistical qualitative analysis methods, where the data reduction component and data presentation are carried out simultaneously with the data collection process after being collected, so that the three components are analyzed (data reduction, data presentation, drawing conclusions) interact. The results of this study indicate that (1) the process of the eligibility mechanism and the qualifications of coaches and badminton achievement coaching club athletes in Bengkulu City includes PB. Orchid, PB. Porpu, PB. Tupperware is quite decent. (2) The implementation of the physical exercise program has not been going well, in the trainer and athlete sectors. (3) The facilities and infrastructure owned by the badminton achievement coaching club in Bengkulu City are still in the poor category because only PB. Porpu have adjusted the facilities and infrastructure according to PBSI standards while PB. Anggrek and PB.Tupperware still need to be fixed.